2022
DOI: 10.3389/fendo.2022.913345
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of N6-Methyladenosine Associated SNPs as Potential Functional Variants for Type 1 Diabetes

Abstract: ObjectivesN6-methyladenosine (m6A) is essential in the regulation of the immune system, but the role that its single nucleotide polymorphisms (SNPs) play in the pathogenesis of type 1 diabetes (T1D) remains unknown. This study demonstrated the association between genetic variants in m6A regulators and T1D risk based on a case-control study in a Chinese population.MethodsThe tagging SNPs in m6A regulators were genotyped in 1005 autoantibody-positive patients with T1D and 1257 controls using the Illumina Human O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses demonstrated that differentially methylated transcripts were involved in pathways related to immunity, including some closely associated with T1DM [ 81 ]. Chen et al [ 82 ] found that three single nucleotide polymorphisms (SNPs) in the non-coding regions PRRC2A (rs2260051 and rs3130623) and YTHDC2 (rs1862315) were significantly correlated with a risk of T1DM. PRRC2A was highly expressed in the peripheral blood of T1DM patients and involved in the interactions of cytokines with their receptors, cell adhesion and chemotaxis, and neurotransmitter regulation.…”
Section: M6a Methylation In Other Autoimmune Diseasesmentioning
confidence: 99%
“…Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses demonstrated that differentially methylated transcripts were involved in pathways related to immunity, including some closely associated with T1DM [ 81 ]. Chen et al [ 82 ] found that three single nucleotide polymorphisms (SNPs) in the non-coding regions PRRC2A (rs2260051 and rs3130623) and YTHDC2 (rs1862315) were significantly correlated with a risk of T1DM. PRRC2A was highly expressed in the peripheral blood of T1DM patients and involved in the interactions of cytokines with their receptors, cell adhesion and chemotaxis, and neurotransmitter regulation.…”
Section: M6a Methylation In Other Autoimmune Diseasesmentioning
confidence: 99%